The early hydration of metakaolin blended cements by non-contact impedance measurement. (September 2018) - Cai, Rongjin; He, Zhen; Tang, Shengwen; Wu, Tao; Chen, E
Abstract: This paper aims to study the early-age hydration process of metakaolin blended cement pastes. The hydration characteristics of different stages, i.e. first dissolution, acceleration, second dissolution and hardened stage, are analyzed by non-contact impedance measurement (NCIM), X-ray diffraction (XRD), derivative thermogravimetric analysis test (DTG), and Fourier transform infrared spectroscopy (FTIR). Through the comprehensive investigation, the second dissolution stages corresponding to the plateau segments appearing in impedance modulus curves for metakaolin blended cement pastes, seem to be associated with the dissolution behavior of metakaolin in alkaline condition. The larger amount of metakaolin in the paste results in the more distinct plateau or descent segment. Furthermore, 15% metakaolin replacement is most favorable to enhance the hydration rate and broaden the range of pore size distribution of blended cement paste. Meanwhile, the compressive strength, water requirement of normal consistency and setting time of blended pastes are examined to study their macro-physical performances. Highlights: Non-contact impedance measurement (NCIM) is employed to investigate the hydration behavior. Different hydration stages of metakaolin blended cement pastes are divided. The plateaus of impedance curves may be related to the dissolution behavior of metakaolin. 15% metakaolin replacement can enhance the hydration rate and broaden the range of pore size distribution.